2021
DOI: 10.1021/acsami.1c10369
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of Key Structural Components Resulting in Ageing of Supercapacitors and the Related Chemical Ageing Mechanism

Abstract: The research on supercapacitors (SCs) is one of the hot topics in the field of energy storage, and the intrinsic ageing mechanism of SCs is significant from both the economic and the scientific point of view. In this paper, the negative effects of decay of the key structural components on ageing of SCs were investigated by factorial design and analysis of variance (ANOVA). The ANOVA results showed that the degree of the negative influence on ageing of SCs could be ranked in descending order as anode > separato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
3
3
0
Order By: Relevance
“… The increase in the content of various C–F bonds after the floating charge indicates that C–F bonds are more susceptible to forming at positive electrodes and high voltages. Combined with the previous gas components results, it can be concluded that the residual water in the system is oxidized to produce O 2 and H + (Scheme S1) at the positive electrode, which is weak at 2.7 V due to the almost no Raman signal from O 2 (Figure a), as previously reported. , Furthermore, the anion BF 4 – undergoes light hydrolysis to produce H + and F – (Scheme S2), consistent with the previous understanding . The tendency of surface oxygen-containing functional groups to react with H + and F – can facilitate the transformation of C–O/CO into more C–F bonds through fluorination reactions (Schemes S3 and S4). …”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“… The increase in the content of various C–F bonds after the floating charge indicates that C–F bonds are more susceptible to forming at positive electrodes and high voltages. Combined with the previous gas components results, it can be concluded that the residual water in the system is oxidized to produce O 2 and H + (Scheme S1) at the positive electrode, which is weak at 2.7 V due to the almost no Raman signal from O 2 (Figure a), as previously reported. , Furthermore, the anion BF 4 – undergoes light hydrolysis to produce H + and F – (Scheme S2), consistent with the previous understanding . The tendency of surface oxygen-containing functional groups to react with H + and F – can facilitate the transformation of C–O/CO into more C–F bonds through fluorination reactions (Schemes S3 and S4). …”
Section: Resultssupporting
confidence: 89%
“…This difference can be ascribed to the oxidation reactions occurring at the positive electrode (Schemes S5 and S6). Conversely, reduction reactions take place at the negative electrode, converting O–CO/CO to C–CO/CH (Schemes S7 and S8). The absence of the CO 2 signal after the floating charge at 2.7 V can be explained by the occurrence of oxidation reactions at high voltages. Similar mechanisms of CO 2 generation have also been reported. ,, …”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations